Diverse feather shape evolution enabled by coupling anisotropic signalling modules with self-organizing branching programme - Ang Li (Nature Portfolio, 2017)
Asymmetric feather vane shape was a critical innovation in feather evolution and adaptation for flight. Here, Li and colleagues characterize the multi-module regulatory network that controls feather vane shape and underlies feather diversification.